The Effect of The Carbon and Environmental Performance on Sustainability Report - Maya Indriastuti (Universitas Muhammadiyah Surakarta, 2021)
The sustainability report contains information that can help investors predict the company's future ability with its stakeholders' support. This study explains the effect of the carbon performance and environmental performance on sustainability report with financial performance as an intervening variable. The population of this research comprised mining companies listed on the Indonesia stock exchange in 2015-2019. The total samples obtained were 80 companies for five years. All data related to the research variables were processed using the structural equation modelling (SEM-WarpPLS) method. The results of this study indicated that carbon performance had a positive effect on financial performance. Meanwhile, the environmental performance had a negative effect on financial performance. On the other hand, carbon performance and environmental performance did not affect the sustainability report. Financial performance variables could not mediate the variables of carbon performance and environmental performance on the sustainability report.Keywords: Carbon performance, environmental performance, financial performance, sustainability report